Islamic Parenting Values in QS. Luqman Verses 13, 16 and 17 Review of Al-Azhar Tafsir by Buya Hamka and its Relevance to Present Life - Ferdian, Ferdian; Cholidi, Cholidi; Maryamah, Maryamah (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This research is motivated by a lack of awareness and understanding among parents regarding the importance of Islamic parenting; many parents who care for and educate their children are not balanced with religious knowledge and the guidance of the Prophet, which results in acts of bullying and violence in raising children and even causes children to die. This research intends to discover the Islamic parenting values contained in the QS. Luqman verses 13, 16 and 17 Study of Tafsir Al-Azhar by Buya Hamka and its relevance to today's life. This research is qualitative, with library research using the Tahlili interpretation method approach. The primary data source for this research is the Book of Tafsir Al-Azhar by Buya Hamka, which is supported by various literature relevant to the research in the form of books, articles, journals, theses, dissertations, etc. The data analysis technique in this research is a content analysis using the tahlili method. Some of the findings in this research include (1) Islamic parenting values in QS. Luqman verses 13, 16 and 17 of Buya Hamka's Al-Azhar Tafsir Study can be classified into three central values, namely the values of faith, worship and morals. The explanation of these three values includes prohibiting associating partners with Allah, strengthening a human's inner relationship with Allah, doing good deeds and making efforts, establishing prayers, commanding good and evil, and being patient. (2) Islamic parenting values in QS. Luqman verses 13, 16 and 17 of the Tafsir Al-Azhar study will always be relevant in parenting and people's lives because these Islamic parenting values provide strong spiritual and moral guidance in facing various challenges and changing times. By integrating the values of faith, worship, and morals into a parenting approach, parents can guide their children to become religious, responsible, and noble individuals.